Kelly, Kim. Photograph of Phillip O'Brien, Sheila and Bill Kelly, and Reggie Carew performing music. - Heritage NL
Kim Kelly provided a picture of Phillip O'Brien, Sheila and Bill Kelly, and Reggie Carew during a musical perfomance. Phillip is playing the accordion, Sheila and Bill are singing, and Reggie is playing the guitar.